If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -6) + 6 = 4x + -4 Reorder the terms: 2(-6 + x) + 6 = 4x + -4 (-6 * 2 + x * 2) + 6 = 4x + -4 (-12 + 2x) + 6 = 4x + -4 Reorder the terms: -12 + 6 + 2x = 4x + -4 Combine like terms: -12 + 6 = -6 -6 + 2x = 4x + -4 Reorder the terms: -6 + 2x = -4 + 4x Solving -6 + 2x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + 2x + -4x = -4 + 4x + -4x Combine like terms: 2x + -4x = -2x -6 + -2x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -6 + -2x = -4 + 0 -6 + -2x = -4 Add '6' to each side of the equation. -6 + 6 + -2x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = -4 + 6 -2x = -4 + 6 Combine like terms: -4 + 6 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 6=7+k/6 | | y=2.5x+8 | | -2(7x-1)+1=-14x+3 | | 3x+3=240 | | 2x=3+4x+5 | | 7x-6-2x=29 | | 5x-3x+2=8 | | 4(9-x)=24 | | 2(2x+3)-3(x-5)=4 | | 10x-8=40x+10 | | (7x+8)=(9x-4) | | 8x-3=8(x-5) | | -4(1-3p)=-4-2(-p-5) | | x/4=11 | | 12x-83=6x+121 | | -(3x-7)=24 | | 2v-5=-10 | | (x-3)(1-x)=1 | | 3(6-x)=3 | | 12+8x-12x+6=-122 | | 4j=3.6 | | 3(y+2)+y=15-(y-4) | | 6p-6=7p-7 | | 25x+10y=405 | | 3(7-x)=12 | | 8=-4(3x-4) | | -x-6x+7=42 | | 9-3(x-4)=36 | | -62=5x+3 | | 18+2x/3=16 | | 24=(2x-3) | | 3w-3=4w+8 |